Factors Influencing the Incidence of Stunting Among Children Under Five in Tanjung Morawa District, Deli Serdang Regency - Arifah Devi Fitriani; Ratu Kisi Nabila Suprapto; Endang Maryanti (Universitas Ibn Khaldun Bogor, 2026)
According to the World Health Organization (WHO), stunting is a growth and developmental disorder in children caused by chronic malnutrition, recurrent infections, and inadequate psychosocial stimulation, characterized by a height-for-age index of < -2 SD. This study aimed to analyze the factors influencing the incidence of stunting among under-five children in Tanjung Morawa District, Deli Serdang Regency. This study employed an analytical survey with a cross-sectional approach. The sample consisted of 71 mothers with stunted children under five. Data were analyzed using bivariate analysis with the chi-square test and multivariate analysis using logistic regression. The results showed that nutritional intake (p=0.000), personal hygiene practices (p=0.027), utilization of health services (p=0.003), child care practices (p=0.003), and exclusive breastfeeding (p=0.032) were significantly associated with stunting incidence. Multivariate analysis revealed that nutritional intake was the most dominant factor (Exp(B)=31.212). In conclusion, all variables significantly influenced the incidence of stunting, with nutritional intake as the dominant factor. Improving child nutrition should be prioritized as a key strategy in stunting prevention.